Development and characterization of pitaya seed oil-in-water nanoemulsions for cosmeceuticals application - Abd Gani, Siti Salwa; Bidin, Hasmah; Basri, Mahiran; Abd. Malek, Emilia; Ahmed Salama, Mohamed Salama Mohamed (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Pitaya seed nanoemulsions have great potential in cosmetic and pharmaceutical industries due to its higher compositions of essential polyunsaturated fatty acids (Linoleic acid (C18:2) and Oleic acid (C18:1)) and antioxidant compounds (polyphenol). However, to date, there is no report regarding to its preparation in nanoemulsion system for cosmeceuticals application. Therefore, the purpose of this investigation was to prepare the Pitaya seed nanoemulsions and mixed surfactants and to consequently select the best nanoemulsions composition for further studies. The preparation and characterization of oil-in-water nanoemulsions stabilized by xanthan gum were then determined. Two types of nonionic surfactants were selected, namely Tween 80 (T80) and Span 80 (S80). The flow curve of the nanoemulsion always exhibited shear thinning behaviour and obeys the power law viscosity. Then, the formulation was stable at room temperature, 25°C and 45°C, as well as after undergoing thaw cycles test for 3 months which is considered stable for three years.